ESG INTEGRATION AND TRUST IN ISLAMIC INVESTMENT DECISIONS - Saputera, Denny; Chen, Robin; Sukma, Andhi (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2025)
There is little empirical understanding of how the credibility of ESG disclosures is related with investor-level determinants that influence the decision-making, performance, and sustainability impacts of Islamic investors. The present study examines the effects of ESG (Environmental, Social, and Governance) integration, financial literacy, and religious commitment on the investor decision, investment performance, and investment sustainability in an Islamic finance framework. It brings to the fore the intermediating role of trust in ESG disclosure, a critical psychological mechanism in investment behavior that has hitherto not been sufficiently studied in Islamic markets. The study was conducted using a descriptive-quantitative and cross-sectional approach, where 350 individual investors of Shariah-compliant instruments from Indonesia were surveyed through purposive sampling and the data analysis was done using the Partial Least Square Structural Equation Modeling (PLS-SEM) method. Results reveal that ESG integration has a significant positive effect on both decision-making and performance. Financial literacy indirectly promotes trust in ESG disclosures, but has no direct effect on decision-making and performance. Trust was found to be a key mediator between ESG and literacy on one hand and behavioural and performance outcomes on the other. Religious commitment strengthens the impact of ESG and trust on performance and sustainability, and acts as a moderating factor that bridges the gap between ethical considerations and financial decisions. Relationships are stable, and robustness checks indicate low sensitivity; the findings urge regulators to enhance ESG disclosure quality and institutions to align their practices with Islamic moral values.